Responsibilities and Authorities of the Notary for the Legalization of Authentic Deeds - Mella Ismelina Farma Rahayu; Carissa Janice (Law Doctoral Community Service Journal, 2023)
A notary is a public official authorized to do authentic deeds and has other authorities as referred to in this Law or based on other laws. This study aims to determine how a notary’s authority and responsibility as a deed maker is towards parties who do not recognize the deed. This type of research uses a doctrinal type because it is concerned about justice and good faith and aims to review the Notary Office Law. The literature study that will be worked on is legal documents such as the Law on the Position of Notary Public, Jurisprudence regarding related cases, and the decision of the West Jakarta District Court No.547/Pdt.G/2021/PN.Jkt.Brt. Based on the results of this study, it is the authority of the notary as the maker of the deed against parties who do not recognize the deed, stating that both parties have agreed and agreed to and at this moment, make a Sale and Purchase Agreement and Power of Attorney with the agreed terms and conditions. The responsibility of a Notary in doing a deed is the responsibility of a Notary in doing an authentic deed due to negligence in doing a deed. The negligence, in this case, is if a Notary has done a deed not by the applicable regulations.